Bidirectional Energy Transfer Between Electric Vehicle, Home, and Critical Load - Ștefan-Andrei Lupu; Dan Floricău (Energies)
In the transition to a sustainable energy system, the integration of electric vehicles into residential energy systems is an innovative solution for increasing energy resilience and optimizing electricity consumption. This article presents a bidirectional AC/DC converter capable of charging the electric vehicle battery under normal conditions, while providing power to a critical consumer in the event of a power grid outage. The simulations performed show us the functionality of this converter, demonstrating its efficiency in ensuring the continuity of supply.